2023
DOI: 10.1007/s13304-023-01554-z
|View full text |Cite
|
Sign up to set email alerts
|

Neuraxial anesthesia for abdominal surgery, beyond the pandemic: a feasibility pilot study of 70 patients in a suburban hospital

Andrea Romanzi,
Tommaso A. Dragani,
Adele Adorni
et al.

Abstract: The aim of this study is to establish the feasibility of awake laparotomy under neuraxial anesthesia (NA) in a suburban hospital. A retrospective analysis of the results of a consecutive series of 70 patients undergoing awake abdominal surgery under NA at the Department of Surgery of our Hospital from February 11th, 2020 to October 20th, 2021 was conducted. The series includes 43 cases of urgent surgical care (2020) and 27 cases of elective abdominal surgery on frail patients (2021). Seventeen procedures (24.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…We argue that neuraxial techniques can be safely and effectively administered with meticulous planning in frail patients with multiple comorbidities proposed for abdominal surgery when it would be preferable to avoid GA after conducting a comprehensive risk-benefit assessment. Moreover adopting this approach may not only diminish admissions to the Intensive Care Unit, thereby conserving beds for acute and trauma patients and reducing hospitalization costs during periods of resource scarcity and therapeutic constraints [ 8 ], but may also align with the Enhanced Recovery After Surgery (ERAS) concept, promoting rapid recovery and minimizing complications even in the context of open surgery. In our approach to CSE anesthesia, we did not use the "needle-through-needle" technique because failed dural puncture occasionally occurs [ 9 ] and because we consider it crucial to test peridural catheters before using them.…”
Section: Discussionmentioning
confidence: 99%
“…We argue that neuraxial techniques can be safely and effectively administered with meticulous planning in frail patients with multiple comorbidities proposed for abdominal surgery when it would be preferable to avoid GA after conducting a comprehensive risk-benefit assessment. Moreover adopting this approach may not only diminish admissions to the Intensive Care Unit, thereby conserving beds for acute and trauma patients and reducing hospitalization costs during periods of resource scarcity and therapeutic constraints [ 8 ], but may also align with the Enhanced Recovery After Surgery (ERAS) concept, promoting rapid recovery and minimizing complications even in the context of open surgery. In our approach to CSE anesthesia, we did not use the "needle-through-needle" technique because failed dural puncture occasionally occurs [ 9 ] and because we consider it crucial to test peridural catheters before using them.…”
Section: Discussionmentioning
confidence: 99%
“…No adverse respiratory events or hemodynamic instability was observed, and the patient was successfully discharged 12 days after surgery. Romanzi et al, [6] recently reported the feasible use of neuraxial anaesthesia in patients undergoing awake laparotomy. The authors included 43 patients requiring urgent abdominal surgery and 27 cases of elective abdominal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Awake laparotomies using neuraxial anaesthesia could be an innovative alternative to general anaesthesia for emergency abdominal surgery. In fact, even if abdominal surgeries have been traditionally performed under general anaesthesia, neuraxial anaesthesia has been reported as a possible feasible solution to manage high risk patients during emergency surgery [6]. This technique was employed during the COVID-19 pandemic to help prevent aerosolizing the virus during induction of general anaesthesia and the results demonstrated reduced complications and enhanced recovery [7,8].…”
Section: Introductionmentioning
confidence: 99%